EVALUASI PENGELOLAAN LABORATORIUM IPA DI SMA NEGERI SEKECAMATAN TAMBUN UTARA KABUPATEN BEKASI - RINI ROSILAWATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
This study is aimed to obtain information on the discrepancy on the components in the management of science laboratories that have been programmed and implemented in State Senior High School in North Tambun in Bekasi by using the Provus’ Discrepancy Model. The research result shows good category in the equality phase of the management process, such as the competencies of the organizer. Meanwhile, the completeness of administration process, tools, and other equipment is good enough. In the installation phase, the planning is categorized good enough. In the phase of process, the laboratory management is classified good. In the phase of product, that is the students’ satisfaction and their competencies in Science, it was found that there was discrepancy on the service carried out by the staff in the laboratory. The highest level of students’ satisfaction is on the capability of the teacher in handling the practical teaching in the laboratory. The students’ learning competencies is higher than the standard score which was identified earlier.